EFFECT OF NAPHTHALENE ACETIC ACID, CALCIUM, PHOSPHORUS, OR POTASSIUM ON FRUIT QUALITY, ABSCISSION, AND THE SHELF LIFE OF GUAVA FRUITS. - Farag, K. M.; Kassem, H. A. (Emirates Journal of Food and Agriculture, 2017)
Effect of different sources of phosphorus, potassium, or calcium alone or in combinationson ’Manshiya’ clone guava was studied during two successive seasons 1995 and 1996. Naphtalene Acetic Acid (NAA) applications either alone or in combination with the three mentioned minerals were also investigated. At harvest, the data indicated that CaC12 treatment did not result in a significant increase in fruit weight in both seasons. However, the combination of CaC12 plus each of potassium phosphate, calcium phosphate, or NAA caused a significant increase in fruit weight as compared with the control. Similarly, the combination of NAA plus either potassium phosphate, or calcium phosphate, or CaC12 led to a significant increase in fruit weight as compared with the control in both seasons. Fruit firmness at harvest was significantly increased by CaC12 alone or in combination with NAA during both seasons while calcium phosphate was not effective in increasingflesh firmness either alone or plus NAA or potassium phosphate when compared with the control. Moreover, NAA alone was not able to significantly affect fruit firmness at harvest in both seasons.Fruit abscission was significantly reduced by potassium phosphate plus either NAA or CaC12 when compared with NAA or CaC12 alone in both seasons. Calcium phosphate was significantly more effective than CaC12 in reducing fruit abscission in both seasons. Carotenes in the fruit skin at harvestwere not significantly increased by phosphorus sources such as potassium phosphate spray in both seasons as compared with the control. The addition of calcium phosphate to potassium phosphate did not result in a significant increase in carotene contents at harvest. After the shelf life period, NAA alone was not able to retard the loss of fruit firmness when compared with the control. However, the combination of NAA plus CaC12 caused a significant retardation in the loss of firmness in bothseasons. Calcium chloride in addition to either calcium phosphate or potassium phosphate resulted in higher fruit firmness after 7 days on the shelf as’ compared with the control. It could be concluded that the combination of potassium phosphate plus NAA had positive effects on fruit quality and reduction of fruit abscission at harvest. Phosphorus sources, however, such as potassium phosphate were not effective in increasing carotenes at harvest even when combined with NAA or calcium phosphate